Analysis and Optimization on Workspace of 2-PrRS-PR(P)S Parallel Metamorphic Mechanism - Ma Kun; Ma Hongwei; Tian Haibo (Jixie chuandong)
Based on the theory of metamorphic mechanism，a novel parallel metamorphic mechanism of 2-PrRS-PR(P)S is proposed. The revolute pair of two limbs in the proposed mechanism can change its rotation axis to achieve the metamorphic configuration. Firstly，the kinematics inverse solutions of the two working configurations of the 2PrRS-PR(P)S are obtained. Then， the constraints conditions of the mechanism are analyzed. By using the three dimensional search method，the reachable workspace is solved. Finally，the relationship between each of parameters and the workspace in different configurations are analyzed. Aiming at the maximized workspace volume，the optimized structural parameters is obtained by Genetic Algorithm and single variable analysis.